Spectrophotometric evaluation of color errors generated in the visual color duplication procedure for current ceramic veneers - Xue-Dong Bai; Yu-Zhu Yan; Qing Li (Elsevier, 2021)
Background/purpose: Color errors associated with the visual color duplication approach for ceramic laminate veneers are still challenging in esthetic dentistry. The aim of this study is to evaluate color errors generated during traditional visual shade matching approach. Materials and methods: Eighteen stooth-shaped veneer discs (shade A2 and 0.7 mm in thickness) were fabricated using six veneer materials. The veneer specimens placed on five extracted teeth with nominal shade A2 formed veneer-tooth combinations. Color coordinates of the A2 shade tab, the extracted teeth, and the veneer-tooth combinations were measured using a spectrophotometer. Then, the veneers were reduced to 0.5 mm, and 0.3 mm in thickness consecutively. Color measurements were performed repeatedly. Color differences of the extracted teeth to veneer-tooth combinations (ΔEt-v), veneer-tooth combinations to shade tab (ΔEv-s), and translucency parameter (TP) values were calculated and analyzed using Two-way ANOVA. Results: ΔEt-v ranged from 2.0937 to 5.0603 (mean of 3.1833±1.5485). Mean of ΔEv-s was 4.0103±1.8508. ΔEt-v and ΔEv-s values were significantly influenced by veneer material and thickness (P<0.05). TP values decreased gradually with the lessening of veneers thickness. Conclusion: Acceptable color duplication of ceramic veneers cannot be achieved by routine visual shade replica protocols, when the thickness of veneers is less than 0.7 mm. Specified color matching standards for the ceramic veneers are needed.